The Influence of Work Motivation, Integrity, and Work Productivity on The Performance of Civil Servants at The Surabaya City Department of Culture, Youth, Sports, and Tourism - Muhammad Ibnu Hamdani Sunyoto; Emeralda Ayu Kusuma (Devotion : Journal of Research and Community Service, 2026)
The performance of civil servants in the Surabaya City Culture, Youth and Sports, and Tourism Office, which declined during 2023–2024, has become a barrier to the effectiveness of Surabaya's work programs and public services. This study aims to examine the effect of work motivation, integrity, and work productivity on the performance of civil servants at the said department. Furthermore, the research applies a quantitative approach. The population consists of 62 civil servants in the Surabaya City Culture, Youth and Sports, and Tourism Office. Moreover, a questionnaire was used as the instrument in the data collection technique. The data were analyzed using multiple regression. The results show that work motivation, integrity, and work productivity have a positive and significant effect on the performance of civil servants in the Surabaya City Culture, Youth and Sports, and Tourism Office. The findings indicate that the improvement of civil servants' performance can be achieved through work motivation empowerment, integrity strengthening, and work productivity optimization simultaneously.